2016
DOI: 10.11604/pamj.2016.24.103.8555
|View full text |Cite
|
Sign up to set email alerts
|

Dépistage sérologique de la maladie cœliaque chez des patients marocains atteints de diabète type 1

Abstract: La maladie cœliaque (MC) est l'une des maladies auto-immunes les plus fréquemment associées au diabète de type 1 (DT1). La prévalence de MC dans DT1 varie de 3 à 6%. La présentation clinique de MC dans DT1 est classé comme asymptomatiques dans environ la moitié des cas. L'objectif de notre étude est de déterminer la fréquence des auto-anticorps anti-transglutaminase tissulaire (AtTG) et anti-gliadines (AAG) chez les patients diabétiques de type 1 dans le but de recommander une éventuelle biopsie jéjunale et d'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Our results display a relatively high prevalence of CD-specific auto-antibodies in Moroccan T1D patients. Actually, a similar Moroccan study has shown a higher rate of tTGA positivity (13%), but regarding the very small sample of adult T1D patients studied (31 cases), these data seem to overestimate the real prevalence of associated auto-antibodies to CD [4]. In contrary and in a similar context, Azzi et al [5] reviewed the records of 720 T1D pediatric patients and concluded a biopsy-proven CD prevalence of 3.05%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results display a relatively high prevalence of CD-specific auto-antibodies in Moroccan T1D patients. Actually, a similar Moroccan study has shown a higher rate of tTGA positivity (13%), but regarding the very small sample of adult T1D patients studied (31 cases), these data seem to overestimate the real prevalence of associated auto-antibodies to CD [4]. In contrary and in a similar context, Azzi et al [5] reviewed the records of 720 T1D pediatric patients and concluded a biopsy-proven CD prevalence of 3.05%.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis gathering 27 studies with a total of 26,605 T1D patients, Elfström found that the overall prevalence of biopsy-proven CD is almost 6% [3]. Till now, there are few relevant published data about the prevalence of CD in the Moroccan general population and also in common clinical conditions usually associated with CD such as diabetes or autoimmune thyroiditis (AIT) [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…discuss the prevalence of the CD-T1DM association in different areas of the world, by comparison with the Moroccan population. It also highlights the importance of CD screening in susceptible patients, especially due to the long-term risk of lymphoma or adenocarcinoma ( 213 ).…”
Section: Atypical Forms Of Celiac Diseasementioning
confidence: 99%